Concise enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol via Co-catalyzed HKR of anti-(2SR, 3RS)-3-methoxy-3-phenyl-1, 2-epoxypropane - Kiran, I. N. Chaithanya; Reddy, R. Santhosh; Suryavanshi, Gurunath; Sudalai, Arumugam (Tetrahedron Letters, 2011)
A short, enantioselective synthesis of (+)-goniodiol and (+)-8-methoxygoniodiol, cytotoxic styryllactones, has been achieved in high optical purities (99% ee). The strategy employs Co-catalyzed HKR of racemic anti-(2SR, 3RS)-3-methoxy-3-phenyl-1,2-epoxypropane and Lewis acid-mediated diastereoselective allylation of aldehyde as chiral inducing key reactions. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Allylation; diastereoselectivity; Hydrolytic kinetic resolution; Racemic anti-epoxide; Styryllactones